2021
DOI: 10.1007/s00402-021-04119-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage total hip arthroplasty after failed fixation of proximal femoral fractures: an increased risk for periprosthetic joint infections?

Abstract: Background Higher complication rates have been reported for total hip arthroplasty (THA) after osteosynthesis of proximal femur fractures (PFF). This study evaluated the infection risk for conversion of internal fixation of PFF to THA by a single-staged procedure in the absence of clear infection signs. Methods Patients undergoing a one-staged conversion to THA (2013–2018) after prior internal fixation of the proximal femur were included. Preoperative diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Interestingly, both these patients had previously undergone revision operation from short IM nail to total hip arthroplasty, which was then complicated by distal femur periprosthetic fracture. Revision surgery comes with a significant risk of infection, with one study reporting an infection rate of 5.8% 25 . Our patients had additional risk factors including diabetes, emphysema and renal cancer.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, both these patients had previously undergone revision operation from short IM nail to total hip arthroplasty, which was then complicated by distal femur periprosthetic fracture. Revision surgery comes with a significant risk of infection, with one study reporting an infection rate of 5.8% 25 . Our patients had additional risk factors including diabetes, emphysema and renal cancer.…”
Section: Discussionmentioning
confidence: 75%
“…Different studies reported microbiological results when converting internal fixation to total hip arthroplasty (THA) and when exchanging loosened THA. [16][17][18] Gittings et al reported an 18% infection rate in patients who had undergone THA following a previous hip surgery for a femoral fracture, acetabular fixation, or slipped capital femoral epiphysis. Renard et al 19 detected a 7% incidence of hidden infection among THA aseptic revisions, being this rate higher in patients presenting with dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Then again, Akgun et al reported a 50% rate of positive cultures in a presumed aseptic revision of proximal humerus osteosynthesis. 22,23 Regarding hip surgery, Hemmann et al 16 conducted a study to analyze the safety of a single-stage revision of Total Hip Arthroplasty (THA) in failed fixations of PFFs. They found that 10% of the cases presented with positive microbiological tests despite a lack of clinical signs of infection preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…There is a signi cant risk of infection in revision surgery, with one study reporting a 5.8% rate of infection in revision from IM nail xation to total hip arthroplasty. 21 Additional risk factors in these patients included diabetes, emphysema and renal cancer. Our reduced length of stay and lower rates in morbidity and mortality may be attributable to improved mobility in the immediate post-operative period with NPC xation.…”
Section: Discussionmentioning
confidence: 99%